STATUS ANGKA BEBAS JENTIK KOTA BANDA ACEH SEBAGAI DAERAH ENDEMIS DEMAM BERDARAH DENGUE TAHUN 2014 - Yulidar Yulidar (Universitas Islam Negeri Ar-Raniry, 2017)
One of vector borne deseases which still remains a health problem in Indonesia is dengue fever (DBD). This desease is caused by dengue virus transmitted by Aedes aegypti mosquitoes. One of cities which is endemic for DBD in 2014 was Banda Aceh. The indicator for DBD endemic is based on entomology index. One of entomology index to be measured is the number of mosquito larvae-free. To know the status of mosquito larvae-free number in Banda Aceh, a suvey has been conducted in three subdistricts within Banda Aceh city, namely Banda Raya (Lamlagang village), Ulee Kareng (Ceurih village), and Baiturrahman (Peuniti village). A survey was conducted in 100 houses of every subdistrict. The total of 300 houses were investigated. From 300 houses investigated, there were 158 houses were positively had mosquito larvae. From 860 containers that were found and checked in those three subdistricts, it was found that there were 235 containers were positively contained mosquito larvae. The container which contained mosquito larvae dominantly was bathups inside the houses, there were 48,22% of larvae and 60,47% of pupas. The results showed that the number of mosquito larvae-free for Banda aceh was 47,33% which indicated that it was still below the number of national larvae-free that is > 95%. Therefore, Banda Aceh is still in a high risk of DBD transmission in the future.